If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 7m + -1m Combine like terms: 7m + -1m = 6m 24 = 6m Solving 24 = 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 24 + -6m = 6m + -6m Combine like terms: 6m + -6m = 0 24 + -6m = 0 Add '-24' to each side of the equation. 24 + -24 + -6m = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -6m = 0 + -24 -6m = 0 + -24 Combine like terms: 0 + -24 = -24 -6m = -24 Divide each side by '-6'. m = 4 Simplifying m = 4
| 37/6-23/4 | | 6a+a=245 | | -c+5=1 | | 2=a/3-2 | | -34-9n=8+5n | | 5t+15=10 | | 1/2y-6x=3 | | 3(7x-4)=15 | | 12s+27=111 | | 37/6-28/4 | | K^2-20k+57=6 | | 12x-6x+186=12x+84 | | 72x=y^2 | | K^20k+57=6 | | 5-7r=26 | | 9-15+x=-12 | | 3y+5=8y-22 | | 100=6n+4 | | 4l+2=22 | | 6x+32=-40 | | http://greece.mrdonn.org/alexander.html | | -11=n/15-10 | | 1+-2x=-x^2+10 | | 4z+6=9z-21 | | -42=-7/3n | | 8=5x-48 | | 8u-32=80 | | 25x^2+450x=0 | | 5x-3x-6=-6+4x-2 | | 6+10x=32+6x | | .2x+4=1.6 | | 2.5-(-14.6)= |